2014
DOI: 10.1680/geot.14.p.098
|View full text |Cite
|
Sign up to set email alerts
|

Tolerably mobile subsea foundations – observations of performance

Abstract: Abstract:Increasing demands for oil and gas exploration in deep water with soft seabed conditions are resulting in the size and weight of subsea shallow foundations stretching the capabilities of installation technologies. One innovation to reduce foundation footprints involves designing foundations to move in a tolerable manner to absorb applied loads rather than being engineered to resist these loads and remain stationary. Critical design considerations are the evolution of foundation capacity and the mode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
(17 reference statements)
5
29
0
Order By: Relevance
“…Also included in Fig. 10 are c h values previously derived from piezocone dissipation tests on UWA kaolin (Randolph & Hope, 2004;Colreavy's unpublished data, 2013;Cocjin et al, 2014;Mahmoodzadeh & Randolph, 2014). The c h values estimated in this study agree well with the more recent studies, but are slightly higher than the historical data reported by Randolph & Hope (2004).…”
Section: Interpretation Of Dissipation Test Resultssupporting
confidence: 85%
“…Also included in Fig. 10 are c h values previously derived from piezocone dissipation tests on UWA kaolin (Randolph & Hope, 2004;Colreavy's unpublished data, 2013;Cocjin et al, 2014;Mahmoodzadeh & Randolph, 2014). The c h values estimated in this study agree well with the more recent studies, but are slightly higher than the historical data reported by Randolph & Hope (2004).…”
Section: Interpretation Of Dissipation Test Resultssupporting
confidence: 85%
“…The best fit between the measured piezocone u 2 normalised pore pressure response and the Teh and Houlsby (1991) solution was obtained using c h = 0·42 mm 2 /s, and this is broadly consistent with that obtained by Chow et al (2014) and Cocjin et al (2014) at similar stress levels. It is now even more evident that excess pore pressures dissipate more efficiently around the piezoball than around the piezocone, as both the piezoball mid-face and equator nondimensional times for U = 0·5 are much lower than that for the piezocone, as also established in experimental studies in the centrifuge (Mahmoodzadeh and Randolph, 2014) and the field (Colreavy et al, 2010;Low et al, 2007), and also confirmed by numerical analysis (Mahmoodzadeh et al, 2015).…”
Section: ·5supporting
confidence: 83%
“…Both the experimental data and the finite-element solution exhibit the Mandel-Cryer effect (Cryer, 1963;Mandel, 1950), whereby the pore pressure begins to increase during dissipation before reducing. This effect is due to total stress transfer from the edges to the centre of the foundation (where the pore pressure is measured) brought about by faster consolidation at the foundation edges than at the centre (Cocjin et al, 2014). Time factors T = tc op /D 2 for the experimental dissipation data, which extend to at least U = 0·4, were calculated by selecting operational values of the coefficient of consolidation, c op (where c op is an operative value representative of conditions involving both horizontal and vertical drainage with c v < c op < c h ) that resulted in the best match with the Gourvenec and Randolph (2010) finite-element solution.…”
Section: Piezofoundation Testsmentioning
confidence: 99%
“…The penetration resistance response and the degree of hole-closure were analysed for nine penetrometer tests using a 11?3 mm diameter ball with a 4?8 mm diameter shaft, penetrating a kaolin clay sample with a progressively higher overconsolidation ratio (OCR). A constant penetration rate of 1 mm/s was adopted such that the non-dimensional velocity vD/c v <130 (v is the penetration rate, D is the sphere diameter and c v is the coefficient of vertical consolidation <2?8 m 2 /year (Cocjin et al, 2014)) and the response is primarily undrained (House et al, 2001). A video recording observed the progressive hole-closure during each test and provided a means of determining the depth at which the cavity, formed by the passage of the ball, closed over.…”
Section: Methodsmentioning
confidence: 99%